What Does It Mean To Be Patriotic? Policing Patriotism in Sports and Social Studies Education. Issue 3 (4th May 2019) - Hawkman, Andrea M.; Van Horn, Selena E.
Abstract: Authors discuss the relationship between social studies education and patriotism. The authors share two lesson plans (one elementary and one secondary) that examine the racialized and politicized experiences of three professional athletes, Gabby Douglas, Colin Kaepernick, and Megan Rapinoe. Drawing on tenets of critical race media literacy and conceptual understandings of critical patriotism, this article presents two model lesson plans designed to assist teachers in guiding students toward an understanding of patriotism that is critical in nature through promoting informed action inside and outside the classroom.